2007
DOI: 10.5610/jaee.7.6_17
|View full text |Cite
|
Sign up to set email alerts
|

Development of Structural Health Monitoring System with Smart Sensors and Wireless Network

Abstract: The practical structural health monitoring system is suggested aiming to detect certainly the occurrence of damage and to identify the portion with the degree of damage. Our system is highly reliable and simple of low cost adopting new sensors which translate the measurements to the damage indices and transmit in the minimum amount of data. The developed smart AE(acoustic emission) sensor is useful for local monitoring detecting the crack of concrete, and new smart VA(vibration analyzing) sensor is used for gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Structural health monitoring (SHM) systems can be found in a number of structures including aircraft, ships, and civil structures. To address the limitations of the current wired sensing technologies, the engineering and research communities are exploring new technologies such as wireless sensors and networks that can be placed at remote locations, providing a global view of the structural performance (Lynch and Loh, 2006;En et al, 2010;Park et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural health monitoring (SHM) systems can be found in a number of structures including aircraft, ships, and civil structures. To address the limitations of the current wired sensing technologies, the engineering and research communities are exploring new technologies such as wireless sensors and networks that can be placed at remote locations, providing a global view of the structural performance (Lynch and Loh, 2006;En et al, 2010;Park et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Rice et al (2010) reported health monitoring using the 'Imote2' smart sensor platform on the Stawamus Chief Pedestrian Bridge (located in Vancouver in British Columbia, Canada). Practical aspects of SHM of a building with acoustic and vibration wireless sensors are detailed by En et al (2010). Park et al (2010) reported SHM systems using wireless smart sensor networks for a cable-stayed bridge (484 m long 2nd Jindo Bridge in Korea).…”
Section: Introductionmentioning
confidence: 99%
“…Vibrations in certain low harmonic frequencies can even cause resonance of the structure that can lead to disastrous consequences such as partial or complete collapse. Structural health monitoring (SHM) is adopted as a method that can detect micro-changes inside the structure thus assisting preventive maintenance and issuing alerts for repairs to be conducted ahead of the breakpoint (En et al, 2010). The easiest way to install such an SHM system is to integrate a grid of wired sensors inside the structure during construction.…”
Section: Introductionmentioning
confidence: 99%